(untitled) (Medical Forum Monthly, 2021)
Objective: The main goal of the whole study is comparison of the outcome of diathermy haemorrhoidectomy against scissor dissection Milligan Morgan operation. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Quarter Teaching Hosp. Gujranwala during August 2019 till December 2019. Materials and Methods: Group A combines with Haemorrhoidectomy through diathermy and Group B consolidates Haemorrhoidectomy of Milligan Morgan by utilizing the subjective bit. Results: The data were collected from 100 patients which can be divided into two groups. The mean age of both groups were 40 to 60 years. Out of 29 cases of group A 20 of them were with third degree haemorrhoids and out of 21 cases of group B 17 were suffering from this disease. The calculations have shown that group A was having a mean time operating near to 52.5 and standard deviation was 11.9. Group B had values of 36,6 and 9.8 simultaneously. The blood loss’ mean amount was 51.92ml in group A and standard deviation was 15.68. In B these values were 70.34 and 25.59 simultaneously. Conclusion: It is concluded that diathermy haemorrhoidectomies are without sutures, a technique of haemorrhoidectomy that is closed and depending upon a modified electro-surgical type of unit to gain tissue sealing as well as a sealing of vessel.